Keadilan Distributif dalam Kebijakan BPJS PBI dan Pemutakhiran DTKS:Analisis Sosiologi Kebijakan Sosial - Reza Dwi Fahlefi (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The Contribution Recipient Assistance (PBI) program within the BPJS Kesehatan (Social Security Agency for Health) system is one way the government provides social protection to underprivileged and vulnerable communities. However, the implementation of this policy still faces several issues, particularly related to the accuracy of the Integrated Social Welfare Data (DTKS) as the basis for determining who is eligible to receive assistance. This study aims to analyze distribution equity in the BPJS PBI policy and DTKS updates using a sociology of social policy perspective. The method used is descriptive qualitative with a literature study approach. Information was obtained from scientific journals, government regulations, official agency reports, and policy documents related to BPJS PBI and DTKS. The research findings indicate that the BPJS PBI policy does not fully adhere to the principle of distribution equity due to persistent exclusion and inclusion errors in recipient data collection. Furthermore, weak data synchronization, bureaucratic issues, and unfair access to information prevent some poor communities from optimally obtaining their right to health insurance. Through the sociology of social policy perspective, it is clear that social protection policies are influenced not only by administrative aspects, but also by power relations, bureaucratic structures, and social injustice within society. This study recommends strengthening the DTKS update system, increasing transparency in data collection, and increasing public participation in the data verification process to ensure more accurate and equitable distribution of health assistance.